(untitled) (Global Journal of Management and Business Research, 2021)
Corporate Governance has been framed in organization which basically define relationship between board members, management team and shareholders, to carry out duties at utmost transparency, ethical and accountability. It is always expected that the corporate governance should meet the global standard for better corporate success. Therefore, it is very necessary to have good corporate governance in order to manage effectively in global market. Companies put in lot of effort to build and adopt a good corporate governance model in order to catch the eye of investors. A good corporate governance practice can help companies perform better than competitors and so does it impact on profitability. This research paper focuses on finding the impact on corporate governance practices on profitability of firms. Here statistical methods like descriptive statistics and Pearson correlation methodology are used to find the direct link. Independent variables are board committee, board size, CEO duality, audit committee, non-executive director and dependent variables are PAT, EPS, ROA.